Non habemus papam – the Abdication of Benedict XVI as Depicted in Polish Realisations of the Big Picture Report (Genealogical Contexts) - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article is devoted to outlining characteristics of the big picture report on the basis of publications focusing on the abdication of Pope Benedict XVI. The analysis of this content enables us to determine how the genre functions as a form of media communication relying on exchange of news, and how it exploits the specificity of the internet as a means of transmission. An attempt is made to show how this form of journalistic expression may evolve and to describe its usefulness from the point of view of the audience.